68PC-met mediates invasion and chemotherapy resistance in high grade serous ovarian cancer. (7th November 2019) - Wood, G E; Lockley, M; Kermorgant, S
Abstract: Background: High grade serous ovarian cancer (HGSOC) is characterised by progressive chemo-resistance. Survival in advanced HGSOC is poor and new therapies are urgently required. The receptor tyrosine kinase c-Met, through gene amplification or protein over-expression, has emerged as a major target and mediator of chemo-resistance in HGSOC. Methods: Novel chemo-resistant HGSOC cell lines were investigated for c-Met expression, activation with exogenous HGF and downstream signalling via western blot analysis. c-Met internalisation was assessed with fluorescent confocal microscopy, following staining with c-Met and the endosomal marker EEA-1. Human samples from HGSOC patients were obtained via Barts/UCLH Gynae Tissue Bank. Tissue sections underwent immunohistochemical staining for c-Met. Cancer associated fibroblasts (CAFs) isolated from HGSOC patients' omentum were assessed by ELISA to detect HGF secretion. The effect of c-Met inhibitors on HGSOC cell line c-Met activation, migration, survival and invasion was investigated via western blot, transwell migration assay, cell viability in anoikis (CellTiter-Glo) and organotypic cultures. Results: Immunostaining detected c-Met in HGSOC patient samples, with strong intensity in the malignant epithelial cells, at the plasma membrane but also in the cytoplasm. c-Met expression is significantly increased in novel cisplatin and carboplatin resistant HGSOC cells, versus isogenic parental cells. c-Met activation in HGSOC cells leads to its rapid endocytosis. Impairing endocytosis pharmacologically reduces c-Met signalling. Chemo-resistant HGSOC cells are more migratory and invasive than parental cells. Primary CAFs secrete various levels of HGF as determined by ELISA. CAFs also increase HGSOC cells' invasion in organotypic cultures. Targeting c-Met pharmacologically reduces migration, invasion and survival of chemo-resistant HGSOC cells. Conclusions: This study confirms c-Met as a therapeutic target using in vitro models and human HGSOC tissues. c-Met endocytosis in HGSOC has been illustrated here, for the first time. Further work is ongoing to develop novel biomarkers for accurate patient selection, exploiting c-Met intracellular localisation. Legal entity responsible for the study: The authors. Funding: Barts Charity. Disclosure: All authors have declared no conflicts of interest.